Fast coding unit selection and motion estimation algorithm based on early detection of zero block quantified transform coefficients for high‐efficiency video coding standard. Issue 5 (1st May 2016) - Kibeya, Hassan; Belghith, Fatma; Ben Ayed, Mohammed Ali; Masmoudi, Nouri
Abstract : High‐efficiency video coding (HEVC) is the newest video coding standard developed by the joint video team, consisting of ITU‐T video coding experts group and ISO/IEC Moving Picture Experts Group. The HEVC standard has aggregated an exhaustive algorithm for mode decision based on a recursive quad‐tree structured coding tree block. Moreover, several specific features have been incorporated into the motion estimation (ME) process to improve its coding efficiency. However, they resulted in very high computational complexity. To accelerate the encoding process, fast mode decision algorithms for the partitioning module and also for the ME module were proposed in this study. These algorithms are based on early zero block detection technique. To improve the efficiency of these algorithms, an overall algorithm which combines the two techniques has been implemented. The performance of the proposed algorithm was checked through a comparative analysis in terms of encoding time and compression rate. Compared to HEVC test model 10.0, the authors' proposed algorithms bring a great reduction of the HEVC complexity encoder with a saving time, which can reach 25% in average for different tested videos and a slight coding loss in terms of image quality and compression rate.